Pengembangan Matriks Kompetensi Berdasarkan Sistem Three on Three di PT E-T-A Indonesia - Yuwono, Vicky; -, Felecia (Jurnal Titra, 2013)
The jobs of HRD at PT E-T-A are recruitment, people development, and layoff. PT E-T-A is currently using contract system for production operator. Contract for employement that expired can be extended or not depend on company policy, or company can open recruitment for employee depends on their demand. Solution is needed for production that must go on eventhough human resources changed. This solution is called competency matrix three on three, which one person masters minimal three competencies and one competency is mastered by three persons. The result of the evaluation still hasnât met the requirement of three on three competency matrix, so that there is a few job that canât be changed by the other employee. The causes of this problem are both operators and staff have not mastered certain competency, numbers of staff are limited, and contract expired. The solutions are given to change the staff competency matrix by blocking on competency which is not their own responsibility, make form competency development plan, job rotation schedule, and change how to fill in competency matrix from manually to automatically.